KAJIAN PROGRAM PEMBERDAYAAN EKONOMI KELUARGA UNTUK PENINGKATAN AKSES PANGAN - Dadang Sukandar; Ali Khomsan; Tin Herawati (Food and Nutrition Society of Indonesia, 2009)
The objectives of the study were to identify national programms of family economic empowerment, to analyze social-economics of program participants, to evaluate the family economics program, to analize impacts of family economic programs toward food access and to create recommendation for improving family economic empowerment programs. This study was conducted in Pamijahan sub-dsitrict of Bogor districts and in Bogor Barat and Bogor Utasra sub-district of Bogor municipality in the period of March to November 2009. Sampling method used was stratified random sampling with equal proportion where the total sample size was 48 households. Data collected include household socio-economics, food consumption of before and after programs and bussines input, proceses and output of before and after program. The results show that the input, process and output of the programs i.e. PNPM Mandiri, Garda Emas, P2KP and KUBE were relatyively good. All of the programs are effective because their 1/Cost-Effective are higher than 1. The probability of Garda Emas to be succesfull is highest (0.89), while the probability of Mandiri, Dakabalarea, P2KP, Kube are 0.80, 0.27, 0.36 and 0.72 respectively.